PENGARUH KEPERCAYAAN DIRI DAN SELF REGULATED LEARNING (SRL) TERHADAP MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN UNIVERSITAS NEGERI SURABAYA - Rida Emaniar Yuwanda; Puspasari, Durinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the declining interest in becoming a teacher among Office Administration Education students at Universitas Negeri Surabaya. It aims to analyze the influence of self-confidence and self-regulated learning on students' interest in becoming a teacher. A quantitative explanatory approach was used, with a questionnaire distributed to 126 students selected through proportional stratified random sampling from a population of 187 students, analyzed using multiple linear regression together with validity, reliability, and classical assumption tests. The results show that self-confidence has a negative but not significant effect on interest in becoming a teacher, whereas self-regulated learning has a positive and significant effect. Simultaneously, both variables significantly affect interest in becoming a teacher, with an Adjusted R-square of 0.076, indicating that the two variables explain 7.6% of the variance in interest in becoming a teacher, while the remaining 92.4% is explained by other factors outside the model.